PELAYANAN POS PELAYANAN TERPADU (POSYANDU) TERHADAP PARTISIPASI IBU BALITA DI DUSUN TANDIHAT DESA TAMBUSAI BARAT KECAMATAN TAMBUSAI KABUPATEN ROKAN HULU - Siti Hartinah Nasution; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This reaserch was conducted at Hamlet Tandihat Village Tambusai Barat Subdistrict Tambusai District Rokan Hulu. The purpose of this study is to find out the services provided by the posyandu, level of participation of mothers balita and correlation between posyandu service with level of participation of mothers balita at Hamlet Tandihat Village Tambusai Barat Subdistrict Tambusai District Rokan Hulu. Sample determination technique is total sampling/census and total number of samples is 86 person. The author uses inferential quantitative method by using correlation pearson product moment and data instrument is guided interview, observation, and documentation. Research that has been done to find respondents stating the services provided by the posyandu already good 100,0%. The level of participation of mothers balita in participating on posyandu activities is medium 70,9%. Analysis results correlation between posyandu service with level of participation of mothers balita is classified as strong that is r = 0,628Keywords: Participant, Mother of Balita, Service of Posyandu